Decision-making regarding total knee replacement surgery: A qualitative meta-synthesis - Ong Bie; Jinks Clare; O'Neill Tracey (BMC, 2007)
Abstract Background Knee osteoarthritis is a highly prevalent condition that can result in disability and reduced quality of life. The evidence suggests that total knee replacement surgery (TKR) is an effective intervention for patients with severe knee problems, but there is also an unmet need for this treatment in the UK. To help understand the reason for this unmet need, the aim of this study was to explore the factors that influence the decision-making process of TKR surgery by synthesising the available evidence from qualitative research on this topic. Methods A meta-synthesis was undertaken. This involved sevens steps: getting started, deciding what is relevant to the initial interest, reading the studies, determining how the studies are related, translating the studies into one another, synthesising translations, and finally, expressing the synthesis. Second-order and third-order interpretations regarding decision-making in TKR surgery were drawn from the literature. Results Ten qualitative studies were found and are included in the synthesis. The evidence suggests that social and cultural categories of aging have shaped the expectation of knee osteoarthritis, and this in turn shapes patients' expectations of treatment options. The role of the health care professional was the strongest theme to emerge across all ten studies. Coping strategies and life context determine short and longer-term outcomes of TKR. Conclusion The decision-making process regarding TKR surgery is extremely complex, as patients have weigh up numerous considerations before they can make a decision about surgery. By synthesising ten qualitative studies, we have illuminated the importance of the health care professional during this process.